2022
DOI: 10.1177/10436596221107600
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and Reproductive Health Knowledge, Attitudes, and Self-Efficacy Among Young Adult Filipino American Women

Abstract: Introduction: Little is known about Filipino American women’s (FAW) sexual and reproductive health (SRH). The purpose of this study was to examine the SRH knowledge, attitudes, and self-efficacy among young adult FAW. Method: This was a qualitative, descriptive interpretive design. Four focus group interviews and one individual interview were conducted. Purposive sampling was used for this study. Inclusion criteria were female, Filipino American, between the ages 18 and 24 years old, and be able to understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Given this context, generations of FilAms (from grandparents, parents, and children) unsurprisingly find it difficult to navigate nuanced conversations about sex and women's health (Nagtalon-Ramos et al, 2022). Instead, community-based qualitative studies in Los Angeles revealed that children received most of their fact-based sexual education from schools and friends, choosing largely to omit conversations with their parents and grandparents to avoid conflict.…”
Section: Filam Women's Sexual and Reproductive Healthmentioning
confidence: 99%
“…Given this context, generations of FilAms (from grandparents, parents, and children) unsurprisingly find it difficult to navigate nuanced conversations about sex and women's health (Nagtalon-Ramos et al, 2022). Instead, community-based qualitative studies in Los Angeles revealed that children received most of their fact-based sexual education from schools and friends, choosing largely to omit conversations with their parents and grandparents to avoid conflict.…”
Section: Filam Women's Sexual and Reproductive Healthmentioning
confidence: 99%